New strategies for a sustainable 99mTc supply to meet increasing medical demands: Promising solutions for current problems - Nawar, Mohamed F.; Türler, A. (Frontiers in Chemistry, 2022)
The continuing rapid expansion of 99mTc diagnostic agents always calls for scaling up 99mTc production to cover increasing clinical demand. Nevertheless, 99mTc availability depends mainly on the fission-produced 99Mo supply. This supply is seriously influenced during renewed emergency periods, such as the past 99Mo production crisis or the current COVID-19 pandemic. Consequently, these interruptions have promoted the need for 99mTc production through alternative strategies capable of providing clinical-grade 99mTc with high purity. In the light of this context, this review illustrates diverse production routes that either have commercially been used or new strategies that offer potential solutions to promote a rapid production growth of 99mTc. These techniques have been selected, highlighted, and evaluated to imply their impact on developing 99mTc production. Furthermore, their advantages and limitations, current situation, and long-term perspective were also discussed. It appears that, on the one hand, careful attention needs to be devoted to enhancing the 99Mo economy. It can be achieved by utilizing 98Mo neutron activation in commercial power nuclear reactors and using accelerator-based 99Mo production, especially the photonuclear transmutation strategy. On the other hand, more research efforts should be devoted to widening the utility of 99Mo/99mTc generators, which incorporate nanomaterial-based sorbents and promote their development, validation, and full automization in the near future. These strategies are expected to play a vital role in providing sufficient clinical-grade 99mTc, resulting in a reasonable cost per patient dose.